Influence of Premilling Treatments on Dal Recovery and Cooking Characteristics of Pigeon Pea - Deshpande, S D; Balasubramanya, R H; Khan, Shabina; Bhatt, D K (Journal of Agricultural Engineering, 2007)
Pre-milling treatments play an important role in improving the dal recovery by loosening the husk from the cotyledons. Pre-milling trials conducted on pigeon pea grain employing soyoil-water and CIRCOT microbial consortium treatments showed dal recovery of 67.61 to 70.39% and 71.39 to 73.85%, respectively in comparison to the dal recovery of 63.19 to 66.27% by conventional dal milling method. Further, the range of variation of solid dispersion during the cooking was observed to be 0.24 to 0.80 g/10g for raw grain, 0.27 to 0.85 g/10g for soyoil treated grain and 0.45 to 1.75 g/10g for consortium treated grains. The optimum cooking time was found to be 38 min for soyoil treated grain, 33 min for microbial consortium treated grain as compared to 43 min for raw untreated grain. Based on the results obtained, the microbial consortium pre-milling treatment was observed to be the most appropriate and promising.